High speed - Carey, Craig Robert; Mones, Isidre; Mones, Marc (New York : Scholastic Inc., 2005)
"The awesome vehicles in this book are sleek, fast, and smooth. They$1 (Bre built for maximum speed. Because it takes high speed to get there now!"--Cover back.s
Keywords: Vehicles -- Speed -- Juvenile literature; Motor vehicles -- Juvenile literature; Emergency vehicles; Space vehicles; Transportation